The Effectiveness of Accreditation in Establishing Quality Culture Changes in Community Health Centre: A Case Study in Bali Province - Wulandari, Nyoman Trisna; Darma, Gede Sri (Jurnal Manajemen Pelayanan Publik, 2025)
This study aims to evaluate the effectiveness of accreditation in establishing a continuous quality culture in community health centers (Puskesmas). The research focused on nine community health centers in Bali that have achieved full accreditation and primary accreditation levels. While attaining high accreditation, concerns regarding service quality carried on, as evidenced by increased complaints from Indonesia's National Health Insurance Agency (BPJS) participants and Google reviews and social media. This study employed a qualitative methodology with a case study approach, collecting data through interviews and questionnaires. The findings show that even though nine Puskesmas have achieved high accreditation, they still haven't been able to create an optimal quality culture. Quality planning, quality control, and quality improvement have mostly been limited to ceremonial activities, like signing a collective commitment banner, and still face major challenges in changing mindsets, which is essential for improving the quality culture. So far, the changes achieved through the accreditation process have mostly focused on improving physical infrastructure and facilities. Building a culture of quality requires a long-term process involving active participation and awareness from all stakeholders, following systematic stages step by step.